2019
DOI: 10.1021/acs.jpcc.9b02639
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Investigation of the Structure and Properties of Au Nanoparticles Supported on ZnO

Abstract: We present a first-principles investigation of the structure, stability, and reactivity of Au nanoparticles (NPs) supported on ZnO. The morphologies of supported Au NPs are predicted using the formation energy of Au surfaces and the adhesion energy between Au and the dominant ZnO surfaces exposed on ZnO tetrapods. We show how Zn interstitials (a stable intrinsic defect in ZnO) are attracted toward the Au/ZnO interface and in the presence of oxygen can lead to the encapsulation of Au by ZnO, an effect that is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The effective back spill-over phenomenon aids in adsorption of more oxide species over the surface of ZnO-GNI HNFs. 63 The operando studies based on PL and electrical measurements confirmed the development of barrier potential at the ZnO-GNI heterojunctions, which reduces the emobility and thereby broaden the trap depth (LD) compared to pristine ZnO leading to the band bending, one of the most pertinent phenomena that should be considered during gas sensor development. From the aforementioned experimental evidences, it can be understood that the influence of spill-over and back-spill effects on mechanism, plasmonic properties of Au nanoclusters, DLs defects and ideal band bending phenomenon enhance the rate of electronic sensitization process, apart from the directed electron transport due to the 1D structure of aligned ZnO-GNI HNFs.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 86%
“…The effective back spill-over phenomenon aids in adsorption of more oxide species over the surface of ZnO-GNI HNFs. 63 The operando studies based on PL and electrical measurements confirmed the development of barrier potential at the ZnO-GNI heterojunctions, which reduces the emobility and thereby broaden the trap depth (LD) compared to pristine ZnO leading to the band bending, one of the most pertinent phenomena that should be considered during gas sensor development. From the aforementioned experimental evidences, it can be understood that the influence of spill-over and back-spill effects on mechanism, plasmonic properties of Au nanoclusters, DLs defects and ideal band bending phenomenon enhance the rate of electronic sensitization process, apart from the directed electron transport due to the 1D structure of aligned ZnO-GNI HNFs.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 86%
“…The third peak at 529.1 eV has the lowest binding energy among all three and can be attributed to oxygen bonded to gold . Interestingly, the binding energy of surface oxygen entities in gZnO red-shifts post AuNP deposition, which either signifies AuNPs tailoring the gZnO surface or increased availability of electrons at oxygen sites or both. The red-shift of surface oxygen XPS peak combined with observation of orange photoluminescence in gZnO-AuNP strongly suggest that deposition of AuNPs leads to an abundance of oxygen interstitials in the gZnO lattice. It is known that AuNPs not only promote adsorption of oxygen at the zinc oxide surface but also transfer electrons to adsorbed oxygen atoms and such electron transfer would again red-shift the surface oxygen photoemission spectrum. , Such transfer of electrons would lend an ionic character to the gold atoms at the surface of AuNPs and would be reflected in Au 4f XPS peaks.…”
mentioning
confidence: 97%
“…Interestingly, the binding energy of surface oxygen entities in gZnO red-shifts post AuNP deposition, which either signifies AuNPs tailoring the gZnO surface or increased availability of electrons at oxygen sites or both. The red-shift of surface oxygen XPS peak combined with observation of orange photoluminescence in gZnO-AuNP strongly suggest that deposition of AuNPs leads to an abundance of oxygen interstitials in the gZnO lattice. It is known that AuNPs not only promote adsorption of oxygen at the zinc oxide surface but also transfer electrons to adsorbed oxygen atoms and such electron transfer would again red-shift the surface oxygen photoemission spectrum. , Such transfer of electrons would lend an ionic character to the gold atoms at the surface of AuNPs and would be reflected in Au 4f XPS peaks. The deconvoluted Au 4f XPS spectra of AuNP-coated gZnO show contribution from Au + ions (minor peaks at 84.8 and 88.9 eV corresponding to Au 4f 7/2 and Au 4f 5/2 , respectively), which confirms the electronic interaction between Au and O atoms of AuNPs and gZnO, respectively (Figure S6c).…”
mentioning
confidence: 99%
See 1 more Smart Citation